Structural study, optical properties, thermal stability, and biological activity of a non-centrosymmetric hybrid compound 3,4-Diaminopyridinium perchlorate (3,4-DAPP) - Soulayma Mtar; Sameh Sellami; Nassira Chniba-Boudjada; Mohamed Boujelbene (Results in Chemistry)
In this work, a new hybrid compound3,4-diaminopyridinium perchlorate with the formula (C5H8N3)ClO4 abbreviated 3,4-DAPP was synthesized in aqueous solution by the slow evaporation. It crystallizes in the monoclinic system, with a non-centrosymmetric space group P21 with the following parameters: a = 5.1261 (9), b = 9.3003 (17), c = 8.6659 (16) Å and β = 102.595 (7) °. However, the supramolecular structure was built from perchlorate anions (ClO4)− and diaminopyridinum organic cations (C5H8N3)+ connected with hydrogen bonds to form a three-dimensional network. Fourier transform infrared (FTIR) and Raman spectra indicate that the vibrational modes correspond to both inorganic and organic entities. According to Hirschfeld's analysis, the crystal packing is mainly stabilized by the presence of hydrogen bonds O⋯H (50 %), as well as the crystal void analysis indicates the mechanical stability of the structure. Furthermore, the thermal behavior studied by (TGA-DTA) and differential calorimetry (DSC) appears to have stability up to 280 °C. Additionally, the optical properties were investigated by UV–Vis absorption and photoluminescence spectroscopy, which exhibit emission property, and a band gap energy of 3.9 eV. Finally, biological activity tests revealed that 3,4-DAPP exhibited moderate antibacterial activity, particularly against Bacillus cereus. However, it was less effective than 3,4-diaminopyridine (3,4-DAP) against several other bacteria, indicating that the perchlorate group in 3,4-DAPP may reduce its antimicrobial efficacy.